Landasan Empiris Pengembangan Model Pembelajaran Baru untuk Meningkatkan Literasi Kimia, Kebiasaan Berpikir Ilmiah, dan Keterampilan Proses Sains Siswa Pendidikan Kimia - Faiz Ilham Pratama; Eli Rohaeti; Endang Widjajanti Laksono (Postgraduate, University of Mataram, 2024)
The development of a new learning model to increase chemical literacy skills, scientific habits of mind (SHOM), and science process skills (SPS) of chemistry education students is needed to prepare competent chemistry teacher candidates in the future. Theoretical studies have discussed the low chemistry literacy, SHOM, and SPS of students. This research aims to prove the theoretical study data by looking directly at the conditions of chemical literacy, SHOM, and SPS of chemistry education students. The research took place in four stages: measuring and comparing chemical literacy; measuring SHOM; observing SPS during learning activities in the laboratory; and conducting needs analysis for lecturers. The scores obtained from measuring chemical literacy are very worrying. However, there are significant differences in chemical literacy as the years of study increase. Student SHOM is also still in the medium category and needs to be improved. Student SPS is also still relatively low. Furthermore, the lecturers suggested developing a learning model that could develop these three abilities. The model developed must be suitable for adult learning and be able to develop student abilities